Industrial archaeology : principles and practice - Palmer, Marilyn (Routledge, 1998)
Industrial Archaeology sets out a coherent methodology for the discipline which expands on and extends beyond the purely functional analysis of industrial landscapes, structures and artefacts to their cultural meaning.